Improving Technical and Report Writing Skills of Transition Students by incorporating Solo Taxonomy and Problem-Based Learning - Mogul, Ibtisam Yakub (2020)
Vocational Courses give some amount of technical skills for students to be able to work in industry. However, to achieve higher income and higher sense of achievement, a bachelor’s degree is imperative these days. Many students who have completed their vocational courses thus join Top UP Programme to achieve this goal. In computing curriculum, an advanced module “Web and Systems Based Programming” is introduced to them which has a Summative Assessment that includes a Report and an advanced Website creation. Being from varied universities, their curriculum not necessarily have included the prerequisite modules and skills. These technologies are also important for these Computing would-be-graduate soon for their Employability in Industry. As a tutor and evaluator, it poses a challenging task to make such Top UP students in par with the regular students. The undertaken Action Research (AR) Project aimed to make Top Up students work on the current trends of Web Development Technologies using prerequisite subjects [HTML, CSS, PHP] and Report Writing Skills by applying the curriculum models for this process with SOLO taxonomy and Problem Based Learning. Based on the AR project and from overall assessment, it was realized that the project facilitated the pupils to develop and enhance employability skills, and knowledge of problem-based learning. The product and process curriculum model, problem-based learning, multiple formative feedback and learning through peers promoted the TOP Up learners to come in par with the regular students.